Assembly of the Actin Catalyst WASP by Giant SALR Cluster Formation. Issue 5 (15th March 2019) - Sweatman, Martin B.; Insall, Robert
Abstract: Some structures in living cells behave like organelles, but lack individual membranes. The mechanisms that produce such "membraneless organelles" are not understood, but are commonly thought to involve the formation of separate phases via liquid–liquid phase separation. Here, an alternative mechanism is investigated involving short‐range attraction, long‐range repulsion (SALR) fluids, applied at model biological membrane–cytoplasm interfaces. Using Monte Carlo simulations, it is found that giant SALR clusters can form at the membrane surface even when they are unstable in the bulk, for suitably chosen model parameters. It is also found that the formation and location of giant SALR clusters at the interface can be controlled by a third protein species confined to the membrane surface. This behavior mimics that of WASP puncta at the cell membrane, thought to involve WASP and Nck protein aggregates controlled by clathrin. The SALR mechanism is thus a good model for this system, and for membraneless organelles more generally. Abstract : Membraneless organelles in biological cells are generally thought to form via liquid–liquid phase separation. However, using Monte Carlo simulation, it is shown that the SALR (short‐range attraction, long‐range repulsion) interaction model provides a better description of the physics of one kind of membraneless organelle, known as WASP puncta, at a model cell membrane.